CpG island methylator phenotype, Helicobacter pylori, Epstein-Barr virus, and microsatellite instability and prognosis in gastric cancer: a systematic review and meta-analysis. - Liang Zong; Yasuyuki Seto (PLoS ONE)
Background The controversy of CpG island methylator phenotype (CIMP) in gastric cancer persists, despite the fact that many studies have been conducted on its relation with helicobacter pylori (H. pylori), Epstein-Barr virus (EBV), and microsatellite instability (MSI) and prognosis. To drive a more precise estimate of this postulated relationship, a meta-analysis was performed based on existing relevant studies. Methods We combined individual patient data from 12 studies which involved 1000 patients with gastric cancer, which met the criteria. We tabulated and analyzed parameters from each study, including H. pylori, EBV, MSI, and clinical information of patients. Results The overall OR for H. pylori infection in CIMP positive group vs. negative group revealed that significantly elevated risks of positive H. pylori infection in the former were achieved (OR 2.23 95% CI, 1.25-4.00; P = 0.007, Pheterogeneity = 0.05). Similarly, strong relation between EBV infection and CIMP was achieved by OR 51.27 (95% CI, 9.39-279.86; P<0.00001, Pheterogeneity = 0.39). The overall OR for MSI in CIMP positive group vs. negative group was 4.44 (95% CI, 1.17-16.88; P = 0.03, Pheterogeneity = 0.01). However, there did not appear to be any correlations with clinical parameters such as tumor site, pathological type, cell differentiation, TNM stage, distant metastasis, lymph node metastasis, and 5-year survival. Conclusions The meta-analysis highlights the strong relation of CIMP with H. pylori, EBV, and MSI, but CIMP can not be used as a prognostic marker for gastric cancer.